Implementasi Pembelajaran Sejarah di Homeschooling pada Program Distance Learning (Studi Kasus di Homeschooling Kak SetoTangerang Selatan 2015) - Fitriani Fitriani (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
This research was conducted with the aim of knowing the history of learning implementations in class 12 SMA in homeschooling kak Seto who followed distance learning programs. The object of this study is the class of 12 high school student inhomeschooling Kak Seto, which follows the learning program distance learning or distance learning independently at home. This study uses a case study.The research data obtained from the results of observation, interviews and documents related to the matter or object of research. Results from this study showed that children who choose homeschooling distance learning program perform assisted with the teacing of history most of the internet., accompanied by tutors or parent to complete the task of material portofolio, but the result of the evaluation conduced by the tutor/ teacher management homeschooling kak seto child program the average distance learning obtain satisfactory velue.